2022
DOI: 10.1108/jed-07-2021-0116
|View full text |Cite
|
Sign up to set email alerts
|

Happiness and pro-environmental consumption behaviors

Abstract: PurposeThis paper employs the theoretical foundations for subjective well-being to examine the impacts of two underlying dimensions of subjective well-being (psychological well-being and social well-being) on pro-environmental consumption behaviors (PECBs). In this research, the moderating role of exposure to positive environmental messages on media in the relationship between subjective well-being and PECBs is also examined.Design/methodology/approachThis research uses a quantitative research method with data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 74 publications
4
42
0
Order By: Relevance
“…Second, CFA results also reported that the five-factor measurement model with 36 items represented a great fit: χ 2 (500) = 1383.495; χ 2 /df= 2.767; p < 0.001; GFI = 0.903; AGFI = 0.885; CFI = 0.972; TLI =0.968; NFI = 0.956, and RMSEA = 0.047 (Hair et al, 2020;Szostek et al, 2020; (Figure 2). Moreover, Figure 2 showed that the standardized regression weights of all items were much higher than the cut-off values of 0.5 (Nguyen et al, 2022).…”
Section: Measurement Modelmentioning
confidence: 92%
“…Second, CFA results also reported that the five-factor measurement model with 36 items represented a great fit: χ 2 (500) = 1383.495; χ 2 /df= 2.767; p < 0.001; GFI = 0.903; AGFI = 0.885; CFI = 0.972; TLI =0.968; NFI = 0.956, and RMSEA = 0.047 (Hair et al, 2020;Szostek et al, 2020; (Figure 2). Moreover, Figure 2 showed that the standardized regression weights of all items were much higher than the cut-off values of 0.5 (Nguyen et al, 2022).…”
Section: Measurement Modelmentioning
confidence: 92%
“… Ouyang et al (2022) further confirmed that SWB has a positive impact on both private PEBs and public PEBs among residents of rural China. Nguyen et al (2022) divided SWB into psychological wellbeing and social wellbeing, and used data from Vietnam to prove that two different types of wellbeing both can promote individuals’ pro-environmental consumption behaviors. Nevertheless, the available literature is focused on adults and research on the adolescents has yet to be explored.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A great deal of research has been conducted by scholars around the relationship between SWB and PEBs. Previous studies have focused on whether the correlation between the two is significant ( Kushlev et al, 2020 , 2021 ; Nguyen et al, 2022 ). There is also some literature that further explores how SWB affect PEBs and what the mechanisms of action between the two are ( Wang and Kang, 2019 ; Ouyang et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirically, purchase intention or willingness to pay has been a central concept to understanding behavioural motivation in various marketing fields such as green marketing (Zhao et al, 2018;Saut and Saing, 2021;Nguyen et al, 2022;Mai et al, 2017), consumer purchase for luxury brands and products (Park et al, 2021), B2B organizational behaviours (Wei and Ho, 2019), or online purchase behaviour (Akram et al, 2021). Likewise, consumers' willingness to pay for green building apartments has been studied by many scholars in green building development (e.g.…”
Section: Theoretical Background and Research Framework 21 Green Buildingmentioning
confidence: 99%